2019
DOI: 10.1016/j.jad.2019.03.003
|View full text |Cite
|
Sign up to set email alerts
|

Buffering against maladaptive perfectionism in bipolar disorder: The role of self-compassion

Abstract: Background: Maladaptive perfectionism is a transdiagnostic risk and maintaining factor for a range of mental health conditions, including bipolar disorder (BD). Self-compassion represents a potential protective factor against maladaptive perfectionism, however no studies to date have examined the relationship of these constructs in BD. The aim of the present study was to examine associations between maladaptive perfectionism, self-compassion and symptoms among individuals with BD.Methods: Baseline data were co… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
32
0
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 32 publications
(36 citation statements)
references
References 64 publications
(80 reference statements)
3
32
0
1
Order By: Relevance
“…These studies are linked to the more general theory of Behavioural Approach System (BAS) dysregulation in BD (Uroševi c et al, 2008), according to which individuals with this disorder are hyper-responsive to rewardrelevant environmental cues and this hyper-responsivity might trigger manic or depressive episodes. Contingent self-worth, autonomy, maladaptive perfectionism (Fletcher et al, 2019), ambitious goal setting and emphasis on goal attainment all point to a specific BAS-related cognitive style (Alloy et al, 2009). Pavlova et al (2011) elicited experiences of success or failure using an anagram task and collected implicit and explicit measures of self-esteem before and after.…”
Section: Identity Self-concept and Self-esteem In Bipolar Disordermentioning
confidence: 99%
See 1 more Smart Citation
“…These studies are linked to the more general theory of Behavioural Approach System (BAS) dysregulation in BD (Uroševi c et al, 2008), according to which individuals with this disorder are hyper-responsive to rewardrelevant environmental cues and this hyper-responsivity might trigger manic or depressive episodes. Contingent self-worth, autonomy, maladaptive perfectionism (Fletcher et al, 2019), ambitious goal setting and emphasis on goal attainment all point to a specific BAS-related cognitive style (Alloy et al, 2009). Pavlova et al (2011) elicited experiences of success or failure using an anagram task and collected implicit and explicit measures of self-esteem before and after.…”
Section: Identity Self-concept and Self-esteem In Bipolar Disordermentioning
confidence: 99%
“…The reviewed studies describe ways in which a more positive and developed self‐concept could be promoted. In both conditions, recent studies have shown that self‐compassion and self‐acceptance (for BPD: Donald et al, 2018, for BD: Døssing et al, 2015; Fletcher et al, 2019; Inder et al, 2011; Yang et al, 2020) might have the potential to therapeutically modulate core symptoms of the disorders and lead to recovery. Instead, self‐criticism is negatively associated to recovery in patients with BPD (Donald et al, 2018) and might increase the risk for suicidal ideation in patients with BD (Stange et al, 2015), in synergy with a negative cognitive style and rumination.…”
Section: Implications For Treatment Discussed In the Reviewed Studiesmentioning
confidence: 99%
“…Following best practice, the design framework identifies specific, malleable causal factors (see Figure 2 ), a change mechanism (individual therapies with a recovery focus), and mode of delivery (email-supported web-delivery with social network components). The framework is evidence-informed, insomuch as it synthesises existing BD research into novel adjunctive psychotherapies (6, 28, 52, 53), technological delivery (18, 54), stage-tailoring (9), QoL outcomes (5557), strengths (49, 5860), co-design, and community-based participatory research (61). Note that the final level in the framework of Figure 1 is co-design with consumers: the aim here is not to present a completed intervention, but to present a framework that can form the foundation of a future co-design process to develop such an intervention 5…”
Section: Considerations In Developing An Online Intervention For Younmentioning
confidence: 99%
“…In order to explore how the perfectionism affects depression, lots of empirical studies on mediator or moderator effects within them have been carried out in recent years. Self-esteem, social support, optimism, rumination, immature defenses, self-compassion and maladaptive coping strategies have been respectively reported to be the role of mediator among perfectionism and depression (21)(22)(23)(24)(25). On the other hand, the moderators include life meaning, self-efficacy, self-compassion, and social support (26)(27)(28)(29).…”
Section: Introductionmentioning
confidence: 99%